THE HISTORICAL BACKGROUND OF THE RELATIONS OF UKRAINIAN COSSACKS WITH THE ROYAL AND LOCAL AUTHORITIES IN THE POLISH-LITHUANIAN COMMONWEALTH (SECOND HALF OF16 — MIDDLE OF 17 C.) - Vitalii Shcherbak (Київські історичні студії)
In the article it is analyzed the evolution of relations between the Cossacks and the royal and local authorities in the Polish-Lithuanian Commonwealth during the second half of the 16th — the middle of the 17th century. Its genesis goes back to the days of the Livonian War, when the need for armed contingents led to the creation of the Registry army, giving the Cossacks rights and privileges. It is noted that Zaporozhians refered to “Decree on the Nizov’s Сossacks” as of 1578 in order to grant them «Cossack liberties» under the rule of Stefan Batori. It is emphasized the role of the historical memory of the Zaporozhian Army and its involvement in the implementation of state policy, especially in the international arena. At the same time, there is increasing in tensions between the Registry Cossacks and local noble officials, which had often escalated into the military conflicts.